Pengetahuan Pengemudi Ojek tentang Bantuan Hidup Dasar di Kehidupan Sehari-Hari Setelah iberikan Pelatihan - Nazma, Diani; Trilaksmi, Antin; Panduwati, Lira; Devantoro, M Ridho (Fakultas Kedokteran Universitas Trisakti, 2023)
Background Basic Life Support (BLS) is the first aid required for patient cardiac arrest and respiratory arrest, especially those occurring outside the hospital. In Indonesia, approximately 300,000–350,000 people experience cardiac arrest each year, mainly on the roads due to trauma/accidents. This research aims to determine the influence of BLS training on the knowledge and skills of the general public, especially online motorcycle taxi drivers, in providing first aid for cardiac arrest. Methods This research employs a one-group pre-post test design to compare knowledge of basic life support before and after training. The sample consists of 193 individuals, with sample selection using consecutive non-random sampling, and data collection conducted through interviews using a questionnaire. Results The research findings using the Wilcoxon Signed Ranks Test yielded a P-value of 0.001, indicating the acceptance of the alternative hypothesis (Ha). This result indicates that there is a statistically significant effect of basic life support training on the knowledge of online motorcycle taxi drivers around Jakarta. Conclusions There is a significant effect of basic life support training on the knowledge of online motorcycle taxi drivers as well as increasing the ability to act on BHD in areas around Jakarta.